Designing Cultural-Based Worksheets (LKPD) in Osing Village Culture for Elementary School Geometry Learning - Theo Septohadi; Shabilla Desinta; Soraya Himmah Udhmiyah; Setiyani Setiyani; Dina Pratiwi Dwi Santi (PT Inovasi Pratama Internasional, 2024)
The aim of this research is to be able to use it as a learning resource for elementary school mathematics using the Osing traditional house, and also to introduce the Osing traditional house to the community. This research is qualitative research that uses an ethnographic approach, and also collects data by surveying students while building rooms in Osing traditional houses and also interviews with teachers. The school sample was selected based on student ability, namely students with high, medium and low ability. A sample of 8 grade 5 students were involved in this research. After the data was collected, the survey data was analyzed descriptively, and the interview data was analyzed by data collection and drawing conclusions. Based on the results of student perceptions, with the largest percentage, almost all students were able to work on the LKPD questions given by the author.